Exploring the Interplay Between Creative Self-Efficacy, Mindset, and Creativity in Response to Negative Feedback - Mengrong Liu; Yilai Pei; Weiguo Pang (Behavioral Sciences)
Negative feedback is both common and important in the creative process. However, research has shown inconsistent effects of negative feedback on creativity, and individual characteristics may moderate the impact of negative feedback on creative performance. This study explores how creative self-efficacy and a creative developmental mindset interact to influence creative performance in response to negative feedback. One hundred and twenty-two university students were recruited to complete the Creative Self-Efficacy Scale and the Creative Mindset Scale. They also participated in two Alternative Uses Tasks and one Realistic Presented Problem, both before and after receiving pseudo negative feedback. The results indicated that individuals with high creative self-efficacy and a low developmental mindset generated more Realistic Presented Problem solutions after negative feedback, while those with high creative self-efficacy and a high developmental mindset generated more original Realistic Presented Problem solutions. These findings are discussed in relation to the self-enhancement and self-improvement motivations. Based on our results, the role of creative self-efficacy and a developmental mindset should be considered when delivering negative feedback. Our research also highlights ways to foster creativity in educational and workplace settings.